Long-term stable and sustainable high-strength engineered cementitious composite incorporating limestone powder. (January 2023) - Yu, Kequan; Lin, Manfang; Tian, Likang; Ding, Yao
Abstract: High-strength engineered cementitious composite (HS-ECC) features low water-to-binder ratio and high-volume cement may result in time-dependent increase of matrix fracture toughness, loss of tensile ductility and high environmental impact. Inert limestone powder (LP) partially replacing cement can stabilize the long-term matrix fracture toughness of HS-ECC. In this study, the impacts of high-level replacement of cement with LP on the short- (28 d) and long-term (360 d) microstructure and mechanical properties of HS-ECC were investigated. Despite lower compressive strength, the tensile properties of HS-ECC with higher LP content were found to be more stable. The composite tensile properties can be traced to the fiber/matrix interface properties via a micromechanical model. The stability function of LP on the long-term tensile properties of HS-ECC was experimentally and theoretically verified. Further, the high-level replacement of cement with LP notably enhanced the sustainability of HS-ECC.